Ứng dụng mô hình tham số biến dạng hai chiều để đánh giá chuyển động ngang đứt gãy Sông Hồng - Công, Dương Chí (Vietnam Journal of Earth Sciences, 2005)
The Red River Fault (RRF) is over 1,000 km long, running from Tibet plateau, through Yunnan (China) and North Vietnam into the Bac Bo gulf. It plays an important role in the tectonics of Asia, dividing Sundaland from the south China block. Two dimensional strain parameters are revised and their appli cat ion for estimating horizontal movements across RRF near Thac Ba-Yen Bai from 1963-1983-1994 geodetic time series is shown. At this time no value of shear strain rate larger than 0,6 wad/yr can be found at 95% confidence. From a recent studies one can cdnclude that the RRF did not slip faster than 1 or 2 mm/year between 1994 and 2000.